18F-FDG Positron Emission Tomography – An Innovative Technique for the Diagnosis of a Canine Lameness - Mann, Kelly; Hart, Juliette; Duerr, Felix (Frontiers in Veterinary Science, 2016)
Introduction: Positron emission tomography imaging with fluorine-18-fluorodeoxyglucose (18F-FDG) is widely known for its use in the diagnosis and tracking of primary and metastatic tumors via uptake and retention of the radiopharmaceutical by hypermetabolic cells. 18F-FDG is also used to study the normal physiology of glucose uptake, metabolism, and muscle activity during and after exercise. Background: A pilot study adding PET imaging to the diagnostic evaluation of canine patients undergoing computed tomography (CT) for mild or intermittent fore- and hind-limb lameness is ongoing. Dogs with an observable (grade 1-2/5) lameness that have undergone routine radiography and complete physical examination by board-certified veterinary surgeons and sports medicine and rehabilitation specialists are enrolled. Each patient undergoes force plate analysis and leash-walking for 15 minutes prior to premedication and induction of general anesthesia for the PET-CT exam. 18F-FDG is injected intravenously and a whole body PET exam is conducted after one hour of radiopharmaceutical uptake time. Standard algorithm, whole body pre- and post-contrast CT exams and focused, standard and bone algorithm CT scans of the fore- or hind-limb areas of interest are obtained concurrently. Abnormal PET-CT findings are further investigated with additional diagnostic imaging or at surgery (e.g., ultrasound, MRI, arthroscopy). Discussion: This case report uses a canine patient referred for forelimb lameness to illustrate the role of advanced imaging in a diagnostic plan and to discuss a recommended PET-CT procedure for lameness evaluation. The strengths and limitations of molecular imaging and the implications for judicious use of advanced imaging modalities are discussed in light of common canine musculoskeletal disease presentations and as a value-added supplement to clinical practice. Concluding Remarks: 18F-FDG PET-CT adds valuable physiologic and anatomic information to the diagnostic evaluation of patients presenting with indistinct or intermittent clinical signs of musculoskeletal inflammation or injury. Tailoring the PET acquisition and radiopharmaceutical parameters allows for detailed information gathering in the realm of exercise physiology and is unlocking a new frontier in the study of canine athletic performance.